Biosynthesis Bacteria Cellulose by Strain of Bacteria Isolated from Native Corrupt Fruit - Li, Chunxia; Zhao, Yuhang; Peng, Fei; Li, Lili; Gao, Ya; Wang, Zhoufeng (Asian Journal of Chemistry, 2014)
Bacterial cellulose (BC) is an interesting biomaterial for widespread applications. However, bacterial cellulose is still expensive compared with other popular organic products and limit its widespread commercial applications. We had isolated a high bacterial cellulose producing strain from local corrupt fruit successfully. The yields of bacterial cellulose from three strains isolated from native corrupt fruit were 3.5, 5.6 and 1.2 g/L, respectively. FT-IR and XRD results indicated the bacterial cellulose fabricated from local strain was typical cellulose I.